Characterization of the complete chloroplast genome of a woody invasive species, Leucaena leucocephala in Korea - Jong-Soo Park; Min-Ju Park; Ho-Rim Hwang; Changkyun Kim (Mitochondrial DNA. Part B. Resources, 2025)
Leucaena leucocephala (Lam.) de Wit 1961 (Caesalpinioideae; Fabaceae) is a shrub or small tree that has various ecological and economic usefulness. Here, we sequenced the complete chloroplast genome of L. leucocephala and analyzed its phylogenomic position in the mimosoid clade. The chloroplast genome of L. leucocephala was 167,423 bp with a pair of inverted repeats of 26,058 bp, a large single-copy region of 95,915 bp, and a small single-copy region of 19,392 bp. Genome annotation predicted 114 genes, including 80 protein-coding, 30 tRNA, and four rRNA genes. The phylogenomic analyses showed that Leucaena was closely related to Dichrostachys in the core mimosoid clade.